ZWYKŁY CZŁOWIEK JAKO BOHATER FILMU DOKUMENTALNEGO - Ziółkowska-Kurczuk, Natasza (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
Article devoted to the problem of character in the documentary. The author reflects on the nature of the film document. The author cites several execution strategies and presents it to its position as a film director. The text makes reference to the concept of studios represented, among others, by the K. Kieślowski, M. Łoziński, K. Karabasz, W. Staroń and the creators of the so-called mainstream cinema family. In a large part of the article the author refers to two examples of films where the director „In Nowicy at the end of the world” and „Six Characters”. The protagonists of these films are ordinary people.